Attitude towards the risk-based approach implementation into the russian healthcare system among employees of medical organizations - S. V. Russkikh; E. A. Tarasenko; T. P. Vasilieva; L. I. Moskvicheva; N. Yu. Gabunia; E. V. Makarova; T. A. Dvornikova; E. A. Putilina (Сибирский научный медицинский журнал, 2024)
Aim of the study was to develop recommendations for improving procedures and unifying the content of risk management of the healthcare system to preserve public health based on an analysis of the opinions of doctors, organizers and experts of the healthcare system. Material and methods. As part of a quantitative online survey conducted from September to December, 2022, 104 respondents working in the healthcare system of the Russian Federation were interviewed. Additionally, 6 in-depth interviews were conducted with the organizers and experts of the healthcare sector as part of a qualitative sociological study. Desk research included analysis of scientific literature, and the regulatory framework related to the introduction of a risk-based approach to healthcare. Results and discussion. The article presents an analysis the perception of risks in healthcare by doctors, organizers and experts at the level of a medical organization, of the healthcare system and of public health (macro level), with the identification and classification of the main risk groups, on the basis of which risk-management’ measures can be built. The results of the study testify to the insufficiently deep introduction of risk management into the management system of medical organizations. The half of the respondents noted the low and extremely low level of risk management principles’ usage in their own organizations (50 % of respondents) and in Russian medical organizations in general (58.6 % of respondents). At the same time, from a third to a half of the participants found that it was difficult to answer about risk management implementation in their organizations, due to the lack of a unified methodology, imperfection of standards and quality control system of this set of measures, lack of specialists who could manage risks, lack of educational activities. To introduce a systematic approach to the unification of risk management processes, it is necessary to develop and approve the methodology of best practices, as well as take care of the training of specialists. Conclusions. In order to implement a systematic approach to the unification of risk management processes, it is necessary to develop and approve a methodology of best practices, as well as to take care of the training of specialists. It is imperative that hospital managers and staff focus on improving the organizational culture of patient safety management as the basis for their mission to preserve public health. It is necessary to continue further research in this direction in order to develop a strategy for countering risks at the level of public health as a medical and social resource of society.